Development and quantitative evaluation of leading and lagging metrics of emergency planning and response element for sustainable process safety performance - Shamim, M.Y. (Elsevier Ltd, 2019)
The process industries are encountering challenges in terms of process disasters; therefore, safety performance has become a focal spot for forthcoming research. Since the process safety management (PSM) has ignored the insight behavior of performance indicators along with their associated metrics. Therefore, it is imperative to develop the leading and lagging metrics for PSM elements. The evaluation of the past major catastrophes reveals that the severity of the disasters depends upon the performance of emergency planning and response (EPR) element of the PSM standard. Although this element is not considered as the contributing factor for the disasters, however, it is more likely to be accepted as mitigation and controlling technique. The current study focusses on the development of leading and lagging metrics for EPR element through the Delphi technique for safer chemical processes. Moreover, a mathematical model, safety performance index (SPI), based on the principle of relative ranking, has been developed for the quantitative evaluation of the developed leading and lagging metrics. Then, the established model has been applied to the case study of a major accident in the process industry, which identified the poor performing metrics in the accident. Hence, this paper is aimed to develop a helpful mathematical tool for quantitative evaluation of the performance of developed leading and lagging metrics in process industries. This will allow more academic consideration and may direct future researchers towards the empirical findings for sustainable safety performance through the proposed conceptual framework. Â© 2019 Elsevier Ltd